2018
DOI: 10.3390/ijms19040982
|View full text |Cite
|
Sign up to set email alerts
|

Multifaced Roles of the αvβ3 Integrin in Ehlers–Danlos and Arterial Tortuosity Syndromes’ Dermal Fibroblasts

Abstract: The αvβ3 integrin, an endothelial cells’ receptor-binding fibronectin (FN) in the extracellular matrix (ECM) of blood vessels, regulates ECM remodeling during migration, invasion, angiogenesis, wound healing and inflammation, and is also involved in the epithelial mesenchymal transition. In vitro-grown human control fibroblasts organize a fibrillar network of FN, which is preferentially bound on the entire cell surface to its canonical α5β1 integrin receptor, whereas the αvβ3 integrin is present only in rare p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 183 publications
(294 reference statements)
3
21
0
Order By: Relevance
“…Although it is well known that the disruption of the collagen III triple helical structure leads to abnormal protein folding, different biological aspects of the vEDS pathogenesis are not yet fully studied. In line with cEDS and hEDS transcriptome profiling, vEDS fibroblasts show the differential expression of several genes encoding structural constituents of the ECM, further supporting the notion that abnormal ECM remodeling is a common denominator of these conditions [50,97].…”
Section: Disturbance Of Ecm Organization Collagens Processing Anmentioning
confidence: 60%
See 4 more Smart Citations
“…Although it is well known that the disruption of the collagen III triple helical structure leads to abnormal protein folding, different biological aspects of the vEDS pathogenesis are not yet fully studied. In line with cEDS and hEDS transcriptome profiling, vEDS fibroblasts show the differential expression of several genes encoding structural constituents of the ECM, further supporting the notion that abnormal ECM remodeling is a common denominator of these conditions [50,97].…”
Section: Disturbance Of Ecm Organization Collagens Processing Anmentioning
confidence: 60%
“…The alteration of the ER redox state may also trigger pro-death signals through the regulation of members of the Bcl-2 family and activation of caspase-dependent apoptosis [106,107]. Consistently, we previously demonstrated that vEDS fibroblasts are in a pre-apoptotic state, due to downregulation of the Bcl-2 anti-apoptotic protein and increased levels of caspase enzymes, and activate a cell survival mechanism through an αvβ3-EGFR crosstalk [45,50]. However, in vEDS cells an enhanced expression of unfolded protein response-related genes was not identified, consistent with the recent findings on cultured dermal fibroblasts from Col3a1 transgenic mice that did not show elevated levels of the unfolded protein response markers Bip and Chop [102].…”
Section: Disturbance Of Ecm Organization Collagens Processing Anmentioning
confidence: 74%
See 3 more Smart Citations